Morphological variability and access to universal grammar in second language acquisition - Oshodi, Boluwaji (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study addresses two controversial issues in second language acquisition ; the source of the variable use of inflections known as morphological variability among L2 learners and the role of UG in the emergence and exibition of this linguistic problem. The claims of the two previous and prominent attempts to account for the source of variability in L2 ; the Failed Functional Feature hypothesis (FFFH) and the Missing Surface Inflection hypothesis (MSIH) have both focused on the syntactic consequences of the problem. The FFFH links the source to representational issue as a result of inability of L2 learners to acquire functional catagories ot instantiated in their L1 while the MSIH ascribes the source to computational issues as a result of performance limitations on production. The current thesis investigates the source of the problem among L2 English through a new account the Feature Conflict and Integation hypothesis (FCIH) which assumes that the main source of morphological variability can be traced to complex cognitive issues which would trigger both computational and representational problems.